2017
DOI: 10.3892/etm.2017.4345
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of α-lipoic acid in hyperuricemia-induced endothelial dysfunction

Abstract: Abstract. The aim of the current study was to determine the effects of α-lipoic acid (LA) on hyperuricemia and endothelial dysfunction, and to uncover the underlying mechanism of its action. A hyperuricemic rat model was established by administration of uric acid (UA) and the rats were orally fed with 2 g/kg/day LA or phosphate-buffered saline. Primary rat aortic endothelial cells were subsequently isolated, and a cell viability assay, apoptosis assay, enzyme nitric oxide synthase (eNOS) activity assay and mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
(37 reference statements)
2
15
0
2
Order By: Relevance
“…Another study reported that UA treatment of rats with middle cerebral artery occlusion enhanced vascular endothelial cell apoptosis ( 4 ). In our study, MAECs treated with different concentrations of UA showed increased expression of BAX and cleaved Caspase-3 and increases in the number of apoptotic cells, which confirmed the role of UA in promoting MAEC apoptosis as reported by a previous study ( 31 ). Furthermore, accumulating evidence has confirmed that miR-214 is a multifunctional miRNA in CVDs ( 32 35 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another study reported that UA treatment of rats with middle cerebral artery occlusion enhanced vascular endothelial cell apoptosis ( 4 ). In our study, MAECs treated with different concentrations of UA showed increased expression of BAX and cleaved Caspase-3 and increases in the number of apoptotic cells, which confirmed the role of UA in promoting MAEC apoptosis as reported by a previous study ( 31 ). Furthermore, accumulating evidence has confirmed that miR-214 is a multifunctional miRNA in CVDs ( 32 35 ).…”
Section: Discussionsupporting
confidence: 92%
“…For this cell line, 300 µM UA in medium already mimicked hyperuricemia and caused obvious cytotoxicity. In agreement with this concept, 0.3 mM (300 µM) UA triggered apoptotic response in human umbilical vein endothelial cells (HUVECs) (31).…”
Section: Discussionsupporting
confidence: 69%
“…Our results are also in accordance with several animal studies. Accordingly, in a study ALA supplementation significantly attenuated oxidative stress and inhibited apoptosis in rat model of hyperuricemia-induced aortic endothelial cells dysfunction (Zou et al, 2017). In another study, dietary ALA could beneficially improve oxidative stress and inflammation and restore nitric oxide (NO) bioavailability in mice exposed to Chronic Intermittent Hypoxia (Badran, Abuyassin, Golbidi, Ayas, & Laher, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Eredményeik alapján az ALA adásával csökkent a ROS szintje, fokozódott az endothelialis NO-szintáz aktivitás, nőtt az ATP és a mitokondriális DNS mennyisége a patkányaorta endothelialis sejtjeiben. 42 Több humán vizsgálat az ALA-kezelés kedvező hatására utalt az endothelműködés tekintetében 1-es és 2-es típusú cukorbetegekben, 43,44 azonban további experimentális és randomizált, placebo-kontrollált vizsgálatok szükségesek az ALA endotheliumra kifejtett hatásának tisztázására DNP-ben.…”
Section: A Pon1 Paraoxonáz Enzim éS Az Endothelialis Diszfunkció…unclassified